EFEKTIVITAS PEMBELAJARAN PAI MENGGUNAKAN MEDIA POWER POINT DENGAN VIDEO MUHASABAH DI KELAS 5 SDIT IQRA’ 1 KOTA BENGKULU - Gurniman Sutarno (UIN Fatmawati Sukarno Bengkulu, 2018)
The purpose of this research is to know the planning, action and result or evaluation of the effectiveness of Islamic Education Lesson Using Power Point Media with Muhasabah Video in the Fifth Grade of Integrated Islamic Elementary School IQRA’ 1 Bengkulu. This research is an evaluative research with descriptive purpose using mixed methodology design. The data was collected by using observation, interview, questionnare, and documentation methodology. In this research, the method of analysis which is used in discussing the problems was descriptive analysis method with triangulation technique. Meanwhile, in quantitative side, the data analysis was by tabulating data according to students’ answer. Furthermore, the researcher in- terprated the data of each indicator researched. The evaluation result of Islamic Education lesson with Power Point media in cognitive aspect was the result of students’ final score report increased 0.7 points. The research result can be concluded that The Effectiveness of Islamic Education Lesson Using Power Point Media with Muhasabah (red: self introspection) Video in the Fifth Grade of Integrated Islamic Elementary School IQRA’ 1 Bengkulu City was categorized effective